Profound childhood deafness in South Africa : a clinical and molecular genetic approach - Gardner, Jessica Clare (Department of Medicine, 2023)
Profound deafness affects approximately one in a thousand infants at birth and two in a thousand children by the age of 6 years. In about half of these children hearing loss is hereditary in origin. In order to elucidate genetic factors in profound childhood deafness in South Africa, a diagnostic screening survey of 1060 hearing impaired children attending five special schools for the deaf was performed and the aetiology of hearing impairment in each child was classified into one of four categories: syndromal genetic deafness (11 % of children), familial non-syndromal deafness (10%), acquired deafness (38%), and deafness of unknown cause (41 %). Selected families with genetic deafness were then appraised clinically, otologically and genealogically for purposes of syndromal delineation. In this way, affected kindreds with four distinct genetic deafness disorders were investigated and a variety of molecular techniques were used in order to localise the causative genes to a chromosomal map position. Where possible, genetic markers that could be used for pre-symptomatic and pre-natal diagnosis were identified. The four disorders studied were sclerosteosis (SCL), autosomal dominant craniometaphyseal dysplasia (AD CMD), familial streptomycin ototoxicity (FSO) and a private syndrome comprising deafness, microtia and facial palsy (DMF). Sclerosteosis is an autosomal recessive disorder of bone overgrowth with a high gene frequency among the Afrikaner population of South Africa. Gene mapping of this disorder has important implications for affected families in terms of pre-natal diagnosis and the detection of asymptomatic gene carriers. In the major theme of the project, twenty-two affected families with sclerosteosis were ascertained and the SCL gene was localised by homozygosity mapping to the long arm of chromosome 1 7 at 17q12-17q21 (maximum LOD score of 6.21 at a recombination fraction [8] of Oat marker locus D17S806). Following localisation of the gene, a bone densitometry study of SCL was undertaken in order to determine whether heterozygous gene carriers manifest significant changes in bone mineral density. The results show that the SCL gene is expressed in the heterozygous state. This finding has positive implications for carrier detection as well as for development of research into treatment of disorders of decreased bone density, such as osteoporosis. The gene for AD CMD in an affected family was linked to a locus on the short arm of chromosome 5 at 5p 15 (maximum LOD score 4.08 at 8 = 0 at marker locus D5S 1963) providing evidence for molecular homogeneity of the condition. Fine mapping of the AD CMD region enabled the candidate gene interval to be narrowed to a distance of 11 cM, between the marker loci D5S2004 and D5S486. A family with a maternally inherited genetic predisposition to streptomycin-induced ototoxicity was found to have an adenine to guanine point mutation at position 1555 of the mitochondrial (mt) genome. This mutation was identified by mtDNA sequencing in a single affected individual and it was then established in the rest of the family by restriction enzyme PCR analysis. Three generation kindred with a unique branchial arch disorder (DMF syndrome), was ascertained and genome screening was initiated in an attempt to map the gene. Positive gene linkage in this family was not established but a large proportion of the genome and several candidate gene loci were excluded. The investigation of the four disorders studied in this project has provided a major step forward in the elucidation of genetic deafness at the molecular level. More importantly, for the affected families concerned, it will enable the implementation of improved management in the form of accurate genetic counselling and presymptomatic and pre-natal diagnosis.